2008
DOI: 10.1007/s10725-008-9322-3
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase and glutathione reductase overexpression in wheat protoplast: photooxidative stress tolerance and changes in cellular redox state

Abstract: In previous works, we have established a correlation between antioxidant system response and tolerance to drought, osmotic stress and photooxidative stress of different wheat cultivars with contrasting drought tolerance. In the present work, a protocol to obtain and transform wheat protoplasts was established. Transgenic protoplasts with Manganese Superoxide Dismutase (Mn-SOD) (E.C.: 1.15.1.1) and Glutathione Reductase (GR) (E.C.: 1.6.4.2) overexpression in chloroplasts were obtained, and their responses to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 55 publications
(54 reference statements)
1
23
0
Order By: Relevance
“…Significantly higher GR activity under PEG stress in WP as compared to other treatments would lead to a greater availability of GSH and thus better ROS detoxification. This is also supported by a previous study which demonstrated that overexpression of GR in wheat protoplast led to an increase in GSH content and GSH/GSSG ratio, which resulted in the maintenance of cellular redox state under drought stress (Melchiorre et al 2009). A better ROS detoxification was also obvious from the decrease in MDA content in WP treatment as compared to other treatments, particularly under PEG stress (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Significantly higher GR activity under PEG stress in WP as compared to other treatments would lead to a greater availability of GSH and thus better ROS detoxification. This is also supported by a previous study which demonstrated that overexpression of GR in wheat protoplast led to an increase in GSH content and GSH/GSSG ratio, which resulted in the maintenance of cellular redox state under drought stress (Melchiorre et al 2009). A better ROS detoxification was also obvious from the decrease in MDA content in WP treatment as compared to other treatments, particularly under PEG stress (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…These radicals are very reactive and would enter numerous further reactions and thereby generate various types of ROS, which would finally destroy the entire photosynthetic apparatus. The first defense line against ROS is dismutation of two superoxide molecules to hydrogen peroxide (H 2 O 2 ) and oxygen by superoxide dismutase (SOD) (Melchiorre et al, 2009). …”
Section: Foliar Application Of Tio 2 Np Under Water-deficit Stressmentioning
confidence: 99%
“…Overexpression of WRKY25 enhanced the expression level of heat-responsive genes HsfA2, HsfB1, HsfB2a, and HSP101 ). Also, expression pattern of glutathione reductases was studied in rice, wheat, barley, and maize during photooxidative stress using northern blot analysis (Melchiorre et al 2009). and Table 3.2 Expression studies of plant microRNAs during abiotic stresses using different transcriptomic approaches…”
Section: Northern Blot Hybridizationmentioning
confidence: 99%